Pengelolaan Kedisiplinan Dengan Layanan BimbinganDan Konseling Di SMK Asta Mitra Purwodadi - Pranawangsih, Rini; , Prof. Dr. Abdul Ngalim, M.M, M.Hum; , Dr. Sabar Narimo, M.M., M.Pd (2016)
This study aimed to describe 1) To know the program planning discipline through guidance and counseling services in vocational SMK Asta Mitra Purwodadi 2) To determine the discipline program implementation through guidance and counseling services in vocational SMK Asta Mitra Purwodadi. 3) To know the discipline program evaluation through guidance and counseling services in vocational SMK Asta Mitra Purwodadi. Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulation. The results of this study were 1) Planning program outlined in the annual program (prota), the semester program (promissory note), monthly programs (probul) 2) Planting discipline students include a) the pilot activities carried out by the father / mother in a simple teacher, b) shake culture at the school gate guarded by teachers picket c) order related to dress, d) Students who are late for BK to request a permit classes, e) Schedule individual counseling services. f) BK / homeroom teacher conduct home visit / call parents when students do not change. 3) Evaluation of the discipline program implemented in each report creation program implementation and thereafter scheduled counseling (in the form of program reports, and follow-up reports eveluasi Counseling). Keywords: counseling, discipline, management